KOMPARASI IKON CABANG OLAH RAGA ASIAN GAMES 2018 JAKARTA-PALEMBANG DAN ASIAN PARA GAMES 2018 - Ika Resmika Andelina (Narada : Jurnal Desain dan Seni, 2019)
Along with the development of technology and the world economy, the use of icons is often found in the creative industries. Icon application can be of various uses, ranging from application icons for devices, sign systems, software, road markings, and others. According to Van Leeuwen, iconography means "writing pictures", often refers to the activity of describing and classifying images. One of the uses of icons in the industrial world can be seen at the Asian Games & Asian Para Games 2018. The icons used at these events are used to represent each sport that is contested. Although it is an icon with the same type of sport, there are different depictions on these icons. This study aims to compare and determine the differences in the 2018 Asian Games & Asian Para Games sports icons, and see which icons can better represent the sport branches they are competing against.